PERANAN PERBANKAN SYARIAH TERHADAP EKONOMI MELALUI PEMBIAYAAN MODAL KERJA UMKM PADA BANK SYARIAH INDONESIA - Egig Islamida Putri; Nanik Kustiningsih (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
This study was conducted to determine the role of Islamic banking in Indonesia through MSME working capital financing. Islamic banking whose main function is as an intermediary is to collect excess funds from surplus parties and transfer them to parties who lack funds in the form of working capital financing, including MSMEs. MSMEs are seen as the driving force of the economy that makes a major contribution to Indonesia's economic development. MSMEs persisted despite the economic crisis. The role of Islamic banks must contribute to the development of MSMEs and continue to improve their management so that they can develop the economy in the future, especially the Islamic economy in Indonesia. This research uses descriptive qualitative research. Primary data sources were obtained by means of interviews or observations through Bank Syariah Indonesia (BSI) customers Krian Sidoarjo and secondary data sources obtained from research using data on the financial statements of Indonesian Islamic Commercial Banks for 2017-2019. The results of this study are that Bank Syariah Indonesia is very helpful for customers, especially Micro, Small and Medium Enterprises (MSMEs) in developing their businesses so that the economy in Indonesia is maintained and increasingly advanced